XSOFT: A generic software teaching and learning model. Issue 3 (4th November 2014) - Radhakrishnan, P.; Kanmani, S.; Nandhini, M.
ABSTRACT The attitude of software learning by students relies on transforming the Learning Model consistently into Software Development Model. The effort and time taken for development of different phases of software, has few issues, in particular, the principles and practices to be followed in academia. To address these issues, a generic software teaching and learning model called eXtreme Software Teaching (XSOFT) is proposed by integrating the essence of the Extreme Programming (XP) method with COSMIC FFP (Common Software Measurement Integration Consortium Full Function Point) Standards. The effectiveness of this proposed model was tested on real time projects assigned to students as a realistic study by selecting them with equal skill and knowledge on programming. They were divided into two groups, such as Pair Programmers and Solo Programmers. The performances of these groups are measured with respect to the trade in person‐days using XSOFT. The empirical results show that the assessment of person‐days are less on pair programming than solo programming and effective programming skill is found with pair programmers. In addition, the robustness of this model are confirmed by the results of another real time project as case study. © 2014 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:432–442, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21613